A new species of freshwater crab of the genus Microthelphusa Pretzmann, 1968 (Crustacea: Brachyura: Pseudothelphusidae) from the Amazon region of Guyana - Pedraza, Manuel; Tavares, Marcos (Zootaxa, 2014)
A new species of freshwater crab, Microthelphusa furcifer, is described and illustrated from the Potaro-Siparuni Kuribrong River in the Guyana Shield (Amazon region of Guyana). The new species can be easily separated from its congeners by the morphology of the first gonopod. The first gonopod of Microthelphusa meansi Cumberlidge, 2007, is illustrated to clarify some aspects of its morphology.